POTENTIAL STUDY OF PHOTOVOLTAIC POWER STATIONS TO MEET ENERGY NEEDS OF FUEL CELL UNITS IN BARU PANDANSIMO BARU BEACH OF BANTUL, YOGYAKARTA - Ely Afridiana Kuncoro; Arief Budiman; Joko Waluyo (Master in Systems Engineering, 2021)
Energy needs are increasing rapidly along with population growth, increasing population activity, and massive development in technology. However, a current energy source is mainly from fossil energy. This condition is inversely proportional to fossil energy stock, decreasing year by year as a natural condition of non-renewable energy. On the other hand, fossil energy damages the environment by its pollution, such as deforestation and air and atmospheric pollution in the form of greenhouse gas emissions. For this reason, the world needs another source of energy that could replace fossil energy as a source and is also environmentally friendly. New and renewable energy could be the solution.Indonesia has plenty amount of new and renewable energy potential. However, renewable energy is weather-dependent, thus requiring storage technology to store the energy. The current common storage technology is battery technology. This technology has some weaknesses: limited capacity, high cost, less flexibility, expensive, and short lifetime. Another storage technology with high flexibility, easy transport, high amount capacity, long lifetime, and wide usage is needed. Hydrogen storage appears to meet all these requirements.This study aimed to calculate the optimum potential of photovoltaic power stations at Baru Pandansimo Beach of Bantul, Yogyakarta, as an energy source to produce hydrogen as a storage energy system. The simulations are done using HOMER software were carried out in three photovoltaic power station scenarios: fixed-tilt, single-axis tracker, and dual-axis tracker, and showed that the fixed-tilt photovoltaic power station scenario is the most optimal design and architecture. With total capacity reaching 7.8 MWp potential to be built at Baru Pandansimo, it could generate 11,657,704 KWh/year electrical energy with an NPC value of USD 8.29 M, and a COE of 0.0420 USD/KWh. This electrical energy could produce 213,288.06 kilograms of H2 at a 2.3 USD/kg production cost.